PELATIHAN PENGELOLAAN SAMPAH ORGANIK MENJADI PUPUK BERSAMA WARGA DESA JATISARI KECAMATAN TAJINAN, KABUPATEN MALANG - Ventivani, Aiga; Rahma, Defirika Duwi; Wicaksono, Hendrik Dwi; Muharram, Akhmad Syahrul (Jurnal Graha Pengabdian, 2023)
A lack of knowledge and skills in processing organic waste in Jatisari Village. It is necessary to conduct a workshop program to increase knowledge and skills in processing organic waste. This program is conducted in the form of socialization and training to increase knowledge on how to process organic waste so that it benefits the welfare of the community, especially farmers. This program included directing the community on how to mix household waste with sugar and EM4. Includes guidance to the community on sorting household waste and how to mix waste with sugar and EM4. The implementation of this training is that partners will be able to do better in processing organic waste properly and correctly.